Hubungan antara Self-Esteem dan Penalaran Moral dalam Pembelajaran Matematika - Anwar Anwar; Ernawati Jais; Sardin Sardin; Dian Ayu Lestari (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Dayanu Ikhsanuddin, 2023)
The formulation of the problem in this study was whether there is a relations self-esteem and moral reasoning in learning mathematics in class VIII students of SMP Negeri 8 Baubau? The pearson of this study was to determine the relationship between sefl-esteem and moral reasoning in learning Mathematics in class VIII students of SMP Negeri 8 Baubau. The type of research is a quantitative study with using the Ex-post Facto method, where the population of this research was all students of class VIII of SMP Negri 8 Baubau wiht a total of 80 students speard over 3 classes. In this study, samples were used was aquestionnaire in learning mathematics. The research data were analyzed by using correlation techniques. From the result of the analysis of correlation techniques, the assessment of self-esteem (X) on moral reasoning inlearning Mathematics (Y) produced a significanse value of 0,000 < 0,05, so it can be concluded that there is a relationsipbetween self-esteem(independent variable) amd moral reasoning in learning Mathematics (dependent variable). The also shows that the two variables have a positive relationship. Thus, the hypothetical decidion that can be taken is that there is arelationship between sef-esteem and moral reasoning ib learning mhatenatics in class VIII Negeri 8 Baubau.